Parental labor market success and children's education attainment - Carsten Ochsen (Universität Rostock, Institut für Volkswirtschaftslehre, 2008)
This study examines the effects of parental labor market activities on children's education attainment. In contrast to the existing literature we consider parental experiences until the children graduate from school. In addition, the effects of the regional economic environment during teacher's decision about the secondary school track are analyzed. Using data drawn from the German Socio-Economic Panel an ordered probit estimator is used to model children's education attainment. With respect to parental labor market participation we find that father's full-time and mother's part-time employment have significant positive effects on children's education attainment. Furthermore, we obtain evidence that the regional GDP growth rate and the regional unemployment rate when children are 10 years old are significantly related to the education that these children ultimately achieve. Our interpretation is that regional economic conditions affect teachers'recommendations for the secondary school track, which are given during the last year of primary school. The results reveal the less successful parents are on the labor market, the lower the average education level of their children. A second important conclusion is that children who live in regions which experience a poor economic performance over a longer period are, on average, less educated than children who live in more affluent regions.
Keywords: I21; J22; E24; J10; J24; 330; education attainment; parental labor supply; macroeconomic uncertainty; family structure; intergenerational link; Kinder; Bildungsniveau; Eltern; Arbeitsangebot; Familiensoziologie; Generationenbeziehungen